2021
DOI: 10.21608/aps.2021.109363.1077
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Proniosomal Gels loaded with Levofloxacin for dermal drug Delivery.

Abstract: Formulation of proniosomal gels and evaluation of their potential in dermal drug delivery of levofloxacin, an antibacterial drug used to treat complicated bacterial infections. Levofloxacin-loaded proniosomal gels were prepared using coacervation phase separation using nonionic surfactants (spans and tweens). Different parameters of the proniosomal gels were evaluated, including particle size (PS), zeta potential (ZP), drug entrapment efficiency percentage (EE%), in vitro drug release, and ex vivo permeation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our findings agreed with Mohtar et al and Gao et al . Furthermore, the amount of Co-SAA showed an insignificant direct relationship with drug release, which could be explained as propylene glycol acts as a penetration enhancer, so increasing its amount may enhance the release of drugs from SLNs. , The kinetic release pattern was best fitted by the Higuchi model, which was consistent with Yasir and Sara, who reported that the Higuchi kinetic model best described the release of haloperidol from SLNs.…”
Section: Resultssupporting
confidence: 91%
“…Our findings agreed with Mohtar et al and Gao et al . Furthermore, the amount of Co-SAA showed an insignificant direct relationship with drug release, which could be explained as propylene glycol acts as a penetration enhancer, so increasing its amount may enhance the release of drugs from SLNs. , The kinetic release pattern was best fitted by the Higuchi model, which was consistent with Yasir and Sara, who reported that the Higuchi kinetic model best described the release of haloperidol from SLNs.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, proniosomes can integrate drug molecules with different solubilities [56]. Also, they enhance the permeation of drugs through the skin due to the presence of surfactants, as they act as penetration enhancers that interact with the stratum corneum lipophilic barrier [57]. However, proniosomes have some limitations as the large particle-size drugs are not easily absorbed through the skin.…”
Section: Proniosomesmentioning
confidence: 99%